Good Policewoman, Good Mother: Stories, Institutions and Political Uses. A Case Study from Buenos Aires Provincial Police - Sirimarco, Mariana (Iberoamericana, 2021)
En agosto de 2018, la foto de una mujer policía amamantando a un bebé abandonado se hizo viral, dentro y fuera de del país, alcanzando una fama tal que le valió el ascenso. Pero su caso no había sido único, revelándonos que tales eventos funcionan ya como tópicos reiterados en la agenda periodística. Este trabajo busca abordar ese caso, para revisar la conjunción de elementos –semánticos, institucionales, coyunturales– con que se construyó el fenómeno social y mediático de esta figura, a la vez que reflexionar sobre los usos políticos e institucionales que, montándose sobre ella, intentan comunicar determinadas concepciones de lo femenino policial.In August 2018, the photograph of a policewoman breastfeeding an abandoned baby in Argentina went viral, in and outside the country. She became so famous that she was promoted. But her case was not unique, showing us that such events are already a recurrent topic in mass media. This paper intends to approach the case, in order to examine the semantic, institutional and temporary elements with which the social and media phenomenon was built. Taking into account its political and institutional uses, this paper also aims to reflect on the way the event was manipulated to communicate specific conceptions regarding feminine policing.Fil: Sirimarco, Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires; Argentin